2004
DOI: 10.1111/j.1432-1033.2004.04418.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards discovery‐driven translational research in breast cancer

Abstract: Discovery‐driven translational research in breast cancer is moving steadily from the study of cell lines to the analysis of clinically relevant samples that, together with the ever increasing number of novel and powerful technologies available within genomics, proteomics and functional genomics, promise to have a major impact on the way breast cancer will be diagnosed, treated and monitored in the future. Here we present a brief report on long‐term ongoing strategies at the Danish Centre for Translational Brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 91 publications
0
34
0
3
Order By: Relevance
“…9). Two proteins (granulocyte-macrophage colony-stimulating factor (CSF) and granulocyte CSF) were identified using the Bio-Rad Bioplex cytokine system as described previously (43). A complete list of proteins detected in the FIF, including cytokines and growth factors, is given in Table I.…”
Section: Protein Profiling Of Whole Fat Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…9). Two proteins (granulocyte-macrophage colony-stimulating factor (CSF) and granulocyte CSF) were identified using the Bio-Rad Bioplex cytokine system as described previously (43). A complete list of proteins detected in the FIF, including cytokines and growth factors, is given in Table I.…”
Section: Protein Profiling Of Whole Fat Tissuementioning
confidence: 99%
“…42 and 43). The TIF is composed of hundreds of proteins that are either secreted, shed by membrane vesicle-like exosomes (75)(76)(77)(78), and/or externalized due to cell death, and preliminary results indicated that the procedure could also be applied to fat tissue (42,43).…”
Section: Cytokines and Growth Factors Secreted By Adipocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible to generate data on many different individual patients to evaluate heterogeneity of tissue profiles. The correlation between genotype and phenotype is still poorly understood and presents a critical challenge to functionally explore mechanisms underlying normal development and disease (46). The phenotypical appearance as seen in a tissue section is evidently based on pattern of expressed proteins within a cell as well as composition of the surrounding micro-environment.…”
Section: Relevance For Clinical Proteomicsmentioning
confidence: 99%
“…The challenge for antibody-based proteomics is to move from a conventional protein-by-protein approach into a high throughput mode to allow chromosome wide analysis (6,7). Technical challenges involve both the antigen production and the subsequent generation and characterization of the antibodies.…”
mentioning
confidence: 99%